Igneous Rock Associations 6. Modelling of Deep Submarine Pyroclastic Volcanism: A Review and New Results - Downey, W.; Lentz, D. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2006)
SUMMARY Deep submarine explosive volcanism has been a topic of controversy for over 20 years. The role seawater pressure plays in inhibiting volatile phase expansion and thereby the depth of submarine explosive eruptions has been the topic of rigorous debate. Until now, the water-vapour curve has been interpreted to mean that the pressure exerted by the overlying seawater column is significant enough to inhibit explosive volcanism at depth. This interpretation assumes that pyroclastic eruptions cannot occur below the critical point of seawater (31.5 MPa or 3.15 km water depth) in the region of the two phase liquid-vapour fields. In fact, most eruptions are interpreted to occur at depths much shallower than 3.15 km, i.e., 0.5 to 1.0 km. What has been overlooked, however, is that volatile phase expansion (specific volume changes in P-T space) plays an important, if not dominant, role in explosive eruptions at depths greater than this critical point. This controversy has led to debate on the environment of formation of volcanic massive sulfide deposits (VMS), because "pyroclastics" are recognized in both the footwall and (or) hangingwall sequences of many of them and are commonly interpreted as reworked, mass-flow deposits from shallow water rather than of deep-water origin, i.e., they have no genetic relationship with the formation and distribution of VMS deposits. To evaluate the possibility that submarine eruptions can occur at depths greater than 1 km, the 1-D numerical model CONFLOW was used. This program uses a specified melt composition, conduit diameter and length, and the initial temperature and pressure at the base of the conduit to calculate the pressure gradient in a conduit of constant cross-sectional area, the enthalpy of the magma, the viscosity of the volatile-magma mixture at specified P-T conditions, the fragmentation depth where the volume fraction gas is 75% (vg ≌ 0.75), and the exit velocity of the volatile-magma mixture. Results of the CONFLOW modelling support our hypothesis that magmatic volatile phase expansion is alone capable of providing enough energy and high enough melt/gas ratio, to initiate submarine pyroclastic eruptions in silicic magmasto the water depths typically associated with VMS genesis, i.e., below the two-phase (liquid-vapour) region for seawater.